The mediating effect of customer satisfaction on the relationship between digital banking service quality and customer loyaltytitle - Hadid, Khattab Ibrahim (2021)
The prevalent rapid changes in the banking service environment are highly competitive and are compelling these banks to focus on digitization to improve their services and product delivery to satisfy the customer's new needs and expectations. Hence, in alignment with these new needs and expectations, this study has been done to investigate the effect of customer satisfaction on the relationship between digital banking service quality and customer loyalty. The research employed a stratified sample method and generated its data using the quantitative approach. The data were collected via the acquired, developed, and validated questionnaire. A total of 384 customers from five major commercial banks in Malaysia responded to the survey. The data were then analyzed using the Partial Least Square Structural Equation Modelling (PLS-SEM) SmartPLS software. Measurement and structural models were assessed for adequate validity and reliability. The findings revealed that digital banking service quality factors comprising reliability, tangibility, responsiveness assurance, and empathy are all positively related to customer loyalty (p<0.05), with the exception of empathy; and to customer satisfaction at p<0.05 with the exception of responsiveness. Meanwhile, customer satisfaction shows a mediating effect on the relationship between reliability, tangibility, empathy, responsiveness assurance, and customer loyalty. The study concluded that digital banking service quality positively and significantly affects customer satisfaction and loyalty in the commercial banking sector. It implies that digital banking services must have modern and effective equipment for processing data and transactions, and the ease of use needs to be designed and built into the digital banking services systems platforms. In addition, an effective digital banking operations tool in the infrastructure platform for digital banking services is essential to ensure that customers can access them quickly and safely.